PENGARUH MODAL DAN TENAGA KERJA TERHADAP PRODUKSI DAN PENDAPATAN PENGERAJIN TENUN DI KECAMATAN SIDEMEN KARANGASEM - Dinata, Ade Rama Wisma; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 11 (2021): VOL 10 NO 11, NOVEMBER 2021 [4406 - 4562], 2021)
This study to analyze effect of capital and labor on the production of weaving craftsmen in Sidemen, Karangasem Regency, analyze effect of capital, labor, and production on income of weaving craftsmen in Sidemen, Karangasem Regency, and to analyze effect of capital and labor to income through the production of weaving craftsmen in Sidemen, Karangasem Regency. The sampling technique was saturated sampling of 50 respondents. The analysis technique used path analysis with SPSS program. The results in this study, several conclusions were obtained, namely (1) Capital and labor have a positive and significant effect on the production of weaving craftsmen, (2) Capital, labor and production have a positive and significant effect on the income of weaving craftsmen and (3) Production mediates the effect capital and labor to the income of weaving craftsmen. Based on the results of the analysis, the Government is expected to be able to maximize its role in overcoming problems in the weaving craft sector so that there is no decrease in buying interest, besides that the government needs to pay attention to providing subsidies to workers to assist the production process of weaving work so that it runs effectively and efficiently.   Keywords: Capital, Labor, Production, Income